A review of complex vector light fields and their applications. (15th November 2018) - Rosales-Guzmán, Carmelo; Ndagano, Bienvenu; Forbes, Andrew
Abstract: Vector beams, and in particular vector vortex beams, have found many applications in recent times, both as classical fields and as quantum states. While much attention has focused on the creation and detection of scalar optical fields, it is only recently that vector beams have found their place in the modern laboratory. In this review, we outline the fundamental concepts of vector beams, summarise the various approaches to control them in the laboratory, and give a concise overview of the many applications they have spurned.